Meningioma in Lateral Cerebellomedullary Cistern without Dural Attachment - Varghese, Prithvi; Kandathil, Julio Chacko; Govindan, Jayasree; R., Rashmi; Jalal, Muhammed Jasim Abdul (Indian Journal of Neurosurgery, 2017)
Intracranial meningiomas without dural attachment are rare and posterior cranial fossa meningiomas without dural attachment are rarer. Such meningiomas are thought to arise from arachnoid cap cells in pial membrane, tela choroidea, or choroid plexus. MRI is the best imaging modality for the diagnosis of meningiomas and typically shows an enhancing, dural based, extra-axial soft tissue mass with a characteristic dural tail. Meningioma without dural attachment should be suspected if the MRI shows a space-occupying lesion having features of a meningioma but without a dural base and dural tail. We report a case of meningioma in the lateral cerebellomedullary cistern without dural attachment.
Keywords: meningioma; lateral medullary cisternal meningioma; meningioma without dural attachment